Rotación de inventarios de productos de consumo masivo y su incidencia en las ventas de la empresa ventascorp S.A para el período 2013-2014, Propuesta de control de inventarios. - Betancourt Guerrero, Carlos Alexander (2015)
VENTASCORP SA, a company dedicated to the distribution of consumer products, has a big problem from its related management of its inventory of products, it has created a customer dissatisfaction, lost money and a poor picture beginnings Company. Given the situation in the company through this research seeks to solve the problem by developing a formal system, socialized and controlled to regulate each of the activities that occur during inventory turnover. This system, analyzing the staff directly involved with the activity and time with customers the company presents the regulations and activities necessary for without delay begins to restructure and reorganize the system which has been working. With the results of the investigation proceeded to develop possible solutions with staff involved so that any decision is reached through mutual agreements and whose application an order is not going but rather as a decision of teamwork. The research could be detected that the problem of inventory turnover is caused by the lack of a formal system to ensure control of the rotation and the handling of products in general. As a result of mismanagement have caused serious problems for the company, as dissatisfaction and loss of customers and reduced revenues from sales, which make us the need for decisions to remedy this situation. For solving the problem encountered the design and implementation of a control system of merchandise inventory turnover of the company suggests